2012
DOI: 10.1111/j.1095-8339.2012.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Elliptic Fourier analysis of leaf shape in southern AfricanStrychnossectionDensiflorae(Loganiaceae)

Abstract: Leaves can be a useful source of taxonomic information in plants particularly when flowers and fruits are absent during certain periods of the year. In this study, we applied an elliptic Fourier analysis (EFA)-based morphometric technique to assess leaf morphological divergence among four species of southern African Strychnos section Densiflorae. Using leaf specimen images from field and herbarium collections, we extracted six shape variables [i.e. principal components (PCs)] from the Fourier coefficients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…The diversity of leaf shape seen across Helianthus appears to arise primarily through the modulation of lateral width, with the first principal components axis explaining 81% of phenotypic variation in leaf shape. Very similar results were found using the same approach for the shrub genus Viburnum (Schmerler et al., ), as well as in southern African members of the genus Strychnos (Adebowale et al., ), for both of which the first principal components axis also captured modulation of leaf width and explained 85–91% of variation in leaf shape. Work in Arabidopsis has shown that four key genes control much of the variation in the leaf length/width ratio by affecting the shape of cells and the number present in the lamina (Tsukaya, ; Nicotra et al., ).…”
Section: Discussionsupporting
confidence: 73%
“…The diversity of leaf shape seen across Helianthus appears to arise primarily through the modulation of lateral width, with the first principal components axis explaining 81% of phenotypic variation in leaf shape. Very similar results were found using the same approach for the shrub genus Viburnum (Schmerler et al., ), as well as in southern African members of the genus Strychnos (Adebowale et al., ), for both of which the first principal components axis also captured modulation of leaf width and explained 85–91% of variation in leaf shape. Work in Arabidopsis has shown that four key genes control much of the variation in the leaf length/width ratio by affecting the shape of cells and the number present in the lamina (Tsukaya, ; Nicotra et al., ).…”
Section: Discussionsupporting
confidence: 73%
“…This method for separating symmetric and asymmetric components of variation has been used in studies to characterize asymmetry and shape variation in plant leaves and other structures [191,260,[299][300][301][302][303][304].…”
Section: Outline Methodsmentioning
confidence: 99%
“…GMM methods are used in many disciplines, within and beyond plant biology, and allow the analysis of the relative positions of landmarks and sets of points used to approximate curves (outlines) and surfaces to quantify size and shape (Jensen 2003, Claude 2008). In recent years botanists have also applied these types of analysis to study the shape of leaves (Jensen 1990, Jensen et al 1993, Viscosi et al 2009a, b, Asanidze et al 2011, Adebowale et al 2012, Morello and Sede 2016, Chitwood and Otoni 2017, De la Paz Pollicelli et al 2018, Li et al 2018, Morello et al 2018, Sandner et al 2019) and other plant organs (Yoshioka et al 2004, Van der Niet et al 2010, Hernández-Ramírez and Aké-Castillo 2014, Ros et al 2014, Bonhomme et al 2017, Savriama 2018, producing informative results with tools which are relatively simple to use. Leaf analysis, compared to the analysis of other plant organs, can, however, with equally simple tools, also provide useful information on the ecology of species.…”
Section: Introductionmentioning
confidence: 99%